Minimum chunk-transmission delay for active safe driving in vehicular ad-hoc networks. (2017) - Chang, Ben-Jye; Liang, Ying-Hsin; Liu, Cheng-Hsin
The active safe driving application offers real-time video streaming services and emergency messages to improve the driving safety in intelligent transportation system (ITS). As the required video and EM quality increasing, the constraints of packet delay, packet loss rate and the bandwidth of packet transmissions become critically in vehicular ad-hoc network (VANET). Multicasting is adopted to reduce the bandwidth waste rate. Although the multicasting VANET can adopt the retransmissions of lost chunks, it yields a long multicasting delay and wastes bandwidth for re-sending the successful video chunks. This paper proposes a peer-to-peer (P2P) network to cooperate with the multicast VANET to reload the lost or unconfirmed chunks timely. The chunk with the least delay to the lost-chunk node is selected as the optimal compensating chunk. Numerical results demonstrate DGR outperforms the compared approaches in successful chunk reload rate, average chunk delay, and chunk delivery ratio. DGR minimises the chunk compensation delay and bandwidth waste rate.